Anxiety and depression in severe maternal morbidity and near miss - Silveira, Monica Silva (2019)
To verify the prevalence of anxiety and depression in women with severe maternal morbidity (near miss), a cross-sectional cohort study was conducted, with 549 women. The Beck Depression Inventory (BDI) and the Anxiety Inventory (BAI) were used. For the statistical analysis, the Pearson chi-square test and the U-Mann-Whitney test besides Odds Ratio and their 95% confidence intervals. There was a higher prevalence and a greater chance of developing anxiety and depression in the SAMM/NM, as well as the positive and significant relationship between both. We consider association from the psychological point of view as a serious and shocking factor in the mental health of women.